Blocking Access to Illegally Published Copyrighted Content - Martinavičiūtė, Simona (Teisė, 2025)
The rapid development of digital technologies and the digitization of copyrighted objects have opened the door to online copyright infringement. The illegal use of copyrighted content (music, films, TV series, sports broadcasts, etc.) is a complex problem that is difficult to tackle in the context of constantly evolving and changing technologies. One of the solutions to protect the interests of creators and legitimate businesses in the digital environment is to limit the availability of illegal content, i.e., blocking access to websites that host illegal content. The implementation of blocking has many practical problems and challenges as it involves competition between fundamental rights, i.e., the freedom of expression and information, the freedom to conduct a business, and the protection of intellectual property, and it is important to strike a balance between these rights. The article analyses the legal regulation of blocking in Lithuania and the decisions of the CJEU related to blocking in copyright infringement cases, which reveals the content of the principle of proportionality and seeks to assess and answer the question of whether the blocking established in Lithuania complies with the principle of proportionality or whether it is appropriate to expand blocking.